Progressive multifocal leukoencephalopathy with gastrointestinal disease in a pediatric kidney transplant recipient. (3rd July 2013) - Burke, M. T.; Trnka, P.; Walsh, M.; Poole, L.; McTaggart, S. J.; Burke, J. R.
Abstract PML is a demyelinating disease of the central nervous system caused by infection with JCV. Several cases of PML in bone marrow and solid organ transplant recipients have been reported in recent years. JCV has been isolated from the gastrointestinal mucosa of immunocompromised patients, but there are no published reports of PML associated with symptomatic gastrointestinal involvement in kidney transplant recipients. We report a case of a nine‐yr‐old girl with a kidney transplant who developed a severe gastrointestinal illness causing pseudo‐obstruction in association with PML. JCV was suspected as the causative agent in this patient by the detection of high JCV titer through PCR analysis of the cerebrospinal fluid and blood and positive staining for simian virus 40 in the colon. JCV intestinal infection should be considered in kidney transplant recipients presenting with intestinal pseudo‐obstruction.